O processo de ocupação urbana de um setor litorâneo de uma capital brasileira: o caso do Bessa em João Pessoa - PB - Sarmento, Marcela Fernandes (2012)
This dissertation examines the process of urban occupation in Bessa, the largest coastal sector (almost 638 hectares) in the city of Joao Pessoa, since its beginning around 1950, until 2011. Previously, that sector was a rural area subdivided in farms, and is now an urban area, composed of three districts - Jardim Oceania, Aeroclube and Bessa - which concentrates over 3.700 buildings. To explain this occupation, the work shows how land was subdivided, by analyzing the eleven subdivisions that were created, and traces a history of the building occupation of the sector, in which some of its stages are examined in depth. The dissertation was based mainly on a survey conducted in the archives of Joao Pessoa city council and on the analysis of subdivision projects, maps of the city and bird-eye photographs. By study the case in question, this dissertation aims at making a significant contribution to the understanding of the urbanization process of coastal areas in Brazilian cities.